Melatonin in horticultural crops: roles in stress tolerance and agronomic applications - Castañares, Jose Luis (Ediciones INTA, 2025)
Melatonin (N-acetyl-5-methoxytryptamine) has emerged as a key bioactive molecule in plants, extending far beyond its well-known role in animals. In horticultural crops, melatonin contributes to physiological regulation, stress mitigation, and improved agronomic performance. This review synthesizes current evidence on melatonin’s biosynthesis, physiological roles, and its effects on tolerance to abiotic stressors such as drought, salinity, and temperature extremes. The review further discusses its application in species including lettuce, tomato, cucumber, and broccoli, with a focus on seed treatment, foliar application, and irrigation. Despite promising outcomes, challenges remain in standardizing doses, validating field efficacy and integrating melatonin into commercial horticulture. Future directions highlight the need for omics-based studies, field-level validations and exploration of melatonin-based technologies to support sustainable crop production.